ANALISIS PENGARUH PERTUMBUHAN THROUGHPUT PETIKEMAS TERHADAP KINERJA OPERASIONAL PELABUHAN - Rorusman Jadid Nurhadi; Romanda Annas Amrullah; Ita Masita (MANAJEMEN DEWANTARA, 2026)
This study is motivated by the growth of container throughput, which may exert operational pressure on port performance if not supported by adequate capacity and management strategies. Therefore, this study aims to analyze the growth of container throughput and its effect on the operational performance of Tanjung Emas Port Semarang, measured using the Berth Occupancy Ratio (BOR) and Yard Occupancy Ratio (YOR). This research employs a quantitative descriptive and explanatory approach using 60 monthly observations from 2020 to 2024, obtained from PT Pelindo Regional III Tanjung Emas Semarang. The data were analyzed using linear time series regression with the inclusion of a lag variable on the dependent variable to capture dynamic effects. Prior to regression analysis, classical assumption tests were conducted, including normality, linearity, autocorrelation, and heteroscedasticity tests. The results indicate that container throughput growth has a positive and significant effect on both BOR and YOR. The YOR model demonstrates a substantially higher adjusted R² compared to the BOR model, suggesting that yard utilization is more responsive to changes in throughput than berth utilization. Although both indicators remain below the optimal threshold of 70%, their upward trends indicate potential future operational pressure. Therefore, proactive and sustainable capacity management strategies are required to maintain port operational performance and prevent over-utilization.